Combinatorial Commons: Social Remixing in a Sharing Economy. (July 2017) - Sanchez, Jose
Abstract : We have entered an era of prosumer culture, where consumers have become producers. This democratisation impacts on all scales of production, including that of architecture. The Polyomino research agenda at the University of Southern California, Los Angeles has been developed by architect, programmer and gaming designer Jose Sanchez to explore ethical forms of participation through growth of the commons, and to reconsider the role of parts in production. Here he explains the issues at stake, as illustrated by some of Polyomino's outcomes.